2022
DOI: 10.3390/jcm11113125
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Grading DR Screening Images among Non-Trained Retina Specialists

Abstract: Poland has never had a widespread diabetic retinopathy (DR) screening program and subsequently has no purpose-trained graders and no established grader training scheme. Herein, we compare the performance and variability of three retinal specialists with no additional DR grading training in assessing images from 335 real-life screening encounters and contrast their performance against IDx-DR, a US Food and Drug Administration (FDA) approved DR screening suite. A total of 1501 fundus images from 670 eyes were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…The possible reasons for variability among graders could be identification and differentiation of subtle DR features (retinal hemorrhages, microaneurysms, hard exudates, new vessels, intraretinal microvascular abnormalities, neovascularization, and surrogate markers of macular edema), variation in image quality due to artifacts, brightness or contrast of images. This has been found in other studies and in other fields of medical imaging as well [ 13 15 ]. Gold standard grading in the current study was done based on a majority decision by the graders.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The possible reasons for variability among graders could be identification and differentiation of subtle DR features (retinal hemorrhages, microaneurysms, hard exudates, new vessels, intraretinal microvascular abnormalities, neovascularization, and surrogate markers of macular edema), variation in image quality due to artifacts, brightness or contrast of images. This has been found in other studies and in other fields of medical imaging as well [ 13 15 ]. Gold standard grading in the current study was done based on a majority decision by the graders.…”
Section: Discussionsupporting
confidence: 83%
“…Inter-grader and intra-grader variability is known among DR graders. Previous studies have shown that inter-grader kappa scores typically range from 0.40 to 0.65 in DR grading [13][14][15][16][17][18][19]. The kappa values for both Polish (0.68-0.90) and Indian graders (0.63-0.91) in the study showed similar variability but were well within the limits showing overall good agreement.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“… Dilation-free funduscopies of DR from ( 122 ). The left image shows multiple small hemorrhages and microaneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…This study analysed locally acquired colour fundus photographs at a tertiary centre in Singapore and revealed a significant range of intra-group and inter-observer variability among human graders with different levels of expertise, particularly in the non-ophthalmology group. Notably, a previous study conducted by Grzybowski A et al demonstrated high variability in diabetic retinopathy grading among non-trained retina specialists [ 25 ]. These findings underscore the need for global improvements in the current grading of diabetic retinopathy severity [ 25 ], especially in centres where human graders are predominantly involved.…”
Section: Discussionmentioning
confidence: 99%